Pengaruh Manajemen Strategi dan Kompetensi Kepala Sekolah terhadap Kinerja Guru - Arina Arina; Yasir Arafat; Syaiful Eddy (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The purpose of this study is to determine the influence of management, strategy, and competency of school principals together on teacher performance in SMP Negeri Sekecamatan Prabumulih Barat. The research was carried out at SMP Negeri Sekecamatan Prabumulih Barat with 2 (two) schools, namely SMP Negeri 4 Prabumulih and SMP Negeri 9 Prabumulih. The method used in this study is a research method with a quantitative approach. The population unit is all teachers spread across the State Junior High School in West Prabumulih District with a total of 116 people. After calculations were carried out with the Slovin formula, the number of samples taken was 90 people. The data collection technique in this study uses questionnaires, observations, and documentation methods. The test of the instrument was carried out to determine the level of validity and reliability of the research instrument. The data prerequisite test uses the Normality Test and the Linearity Test. Data analysis used Multiple Linear Regression, F Test (Simultaneous) and Coefficient of Determination. The result of this study is that the strategic management of the principal and the competence of the principal together have a significant effect on the performance of the guu in the State Junior High School in West Prabumulih District. The conclusion, of all independent variables on the quality of teacher teaching was 90.4% and the remaining 9.6% was influenced by other variables that were not studied in this study. Keywords: Competence; Principal; Strategy Management; Teacher Performance